Developing Indicators to Evaluate Instructor Management of Sports Centers for the People With Disabilities Based on Universal Design Principles in South Korea - Yi, Eunsurk; Shin, Jongseob; Oh, Ahra (Frontiers in Public Health, 2022)
This study was conducted to develop evaluation indicators for instructor-led management of sports centers for the disabled using universal design (UD) principles in South Korea. These indicators have been developed through Delphi technique to identify the effectiveness of an instructor’s management skills. There were 11 documents related to UD used in the literature review, and seven were related to the evaluation index. Through reading and analyzing the relevant contents of the collected literature and many rounds of the Delphi technique, we selected the method and criteria for deriving the evaluation index. In this study, we developed a method that constitutes an evaluation index. The index comprises one evaluation criterion and four evaluation indices. First, for the sub-items of the “recruitment” category, four principles of UD and one supplementary principle of product performance program (PPP) were applied to create items for the evaluation index. Second, the sub-items of the “education” category comprise three evaluation criteria and 10 evaluation indicators. These were applied to the fourth principle of UD and the first and second by-supplementary principles of PPP. The third category, “welfare,” comprised two evaluation criteria and six evaluation indices, and the first by-supplementary principle of PPP was applied to the evaluation indices. The index created for evaluating instructors in sports centers using the method elucidated in this study was adequately reliable. Following a similar method, more evaluation indicators should be developed for evaluations of other functions (such as programs, public relations, safety, and finance) based on the principles of UD.